HETEROGENEITY AS AN ATTRIBUTE OF MODERN SOCIETY - Попков, Д. О. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2018)
The article analyzes the stability of the political order of society in the context of its structure. Based on various theoretical approaches it is shown that the heterogeneity turns to the normative status in modern society. The author grounds ineffectiveness of forced eradication of sub-state collective identities, which were historically formed on the state's therritoty, for establishing political integrity of political order. Due to the author approach to provide effectiveness of the political regime and to save its democratic nature demands finding a balance between unity and diversity of social elements.